Significant reduction in dental cone beam computed tomography (CBCT) eye dose through the use of leaded glasses - Prins, R.; Dauer, L.T.; Colosi, D.C.; Quinn, B.; Kleiman, N.J.; Bohle, G.C.; Holohan, B.; Al-Najjar, A.; Fernandez, T.; Bonvento, M.; Faber, R.D.; Ching, H.; et al. (Oral surgery, oral medicine, oral pathology, oral radiology and endodontics, 2011)
In light of the increased recognition of the potential for lens opacification after low-dose radiation exposures, we investigated the effect of leaded eyeglasses worn during dental cone-beam computerized tomography (CBCT) procedures on the radiation absorbed dose to the eye and suggest simple methods to reduce risk of radiation cataract development. Dose measurements were conducted with the use of 3 anthropomorphic phantoms: male (Alderson radiation therapy phantom), female (CIRS), and juvenile male (CIRS). All exposures were performed on the same dental CBCT machine (Imtec, Ardmore, OK) using 2 different scanning techniques but with identical machine parameters (120 kVp, 3.8 mA, 7.8 s). Scans were performed with and without leaded glasses and repeated 3 times. All measurements were recorded using calibrated thermoluminescent dosimeters and optical luminescent dosimetry. Leaded glasses worn by adult and pediatric patients during CBCT scans may reduce radiation dose to the lens of the eye by as much as 67% (from 0.135 ± 0.004 mGy to 0.044 ± 0.002 mGy in pediatric patients). Leaded glasses do not appear to have a deleterious effect on the image quality in the area of clinical significance for dental imaging.